Beta-glucan effects on 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) toxicity in liver and brain - Turkmen, Nese Basak; Ozek, Dilan Askin; Taslidere, Asli; Dogan, Fatih; Ciftci, Osman (Taylor & Francis Ltd, 2022)
2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) is a common environmental contaminant that is toxic to brain, heart, kidney and liver. TCDD toxicity is due to free radical formation. Beta-glucan is an antioxidant that exhibits beneficial effects on health. We investigated the effects of beta-glucan on brain and liver tissues of rats with TCDD induced toxicity. We used female rats divided into four groups: control, TCDD group treated with TCDD 2 mu g/kg/week, beta-glucan group treated with 50 mg/kg/day beta-glucan for 3 weeks, TCDD + beta-glucan group treated with 2 mu g/kg/week TCDD and 50 mg/kg/day beta-glucan together for 3 weeks. We found that the thiobarbituric acid reactive substance (TBARS) levels were increased significantly in the TCDD group compared to the other groups. Glutathione (GSH) levels, and superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) activities were reduced in the TCDD group compared to the control group. SOD, CAT, GPx activities and GSH levels were increased in the TCDD + beta-glucan group. Histopathological observations were consistent with our biochemical findings. The oxidative stress and histopathology caused by TCDD were ameliorated by beta-glucan treatment. Beta-glucan should be explored for preventing brain and liver damage caused by TCDD toxicity.
Keywords: Beta-glucan; brain damage; liver damage; oxidative stress; rats; 2; 3; 7; 8-tetrachlorodibenzo-p-dioxin (TCDD)